The Development of Thematical Textbooks with Cognitive Perspective Facilitated by Barcode to Improve the Children’s Vocabulary - Slamet, Sri; Wardhani, Junita Dwi; Katoningsih, Sri; Fitriyah, Qonitah Faizatul; Adityarini, Heppy (Universitas Muhammadiyah Surakarta, 2024)
Purpose: The lack of high-quality English textbooks has contributed to vocabulary de-ficiecies among kindergarteners. The survey resulted that children's learned languages might be forgotten after a few days. This study aimed to conduct a study to identify and assess the standard of English textbooks already in use as well as to created textbooks that should be used in Aisyiyah Kindergarten (TK Aisyiyah) in Surakarta. Methodology: In order to address this issue, design-based research (DBR) was used in this study. The development stage and the analysis stage of real-world problems were the two stages used in the research process. Results: The first findings indicated that there were benefits and drawbacks to the previously employed textbooks. The second stage of book production in-volved keeping the positive aspects of the first book, reducing or even get-ting rid of its negative aspects, adding bar-code, and researcher-initiated fea-tures. These components had been adjusted for the cognitive viewpoint. Of course, conversations and focus groups with instructors and academics, as well as expert reviews, went into creating this textbook prototype. Applications/Originality/Value: Following the discussion and focus group discussion (FGD), the textbook would be prepared for the Aisyiyah Kindergarten.